Types of urinary incontinence in Bangladeshi women at midlife: Prevalence and risk factors. (October 2018) - Islam, Rakibul M.; Bell, Robin J.; Hossain, Mohammad B.; Davis, Susan R.
Highlights: Urgency urinary incontinence was the most prevalent form of UI amongst pre-and postmenopausal midlife Bangladeshi women. The overall prevalence of UI was lower than that reported for developed countries. Being postmenopausal, multiparous, obese, and employed outside home were associated with urgency UI. Abstract: Objective: To determine the prevalence of, and risk factors for, sub-types of urinary incontinence (UI) in a nationally representative sample of midlife Bangladeshi women. Methods: Bangladeshi women, aged 30–59, recruited by multi-stage cluster sampling, completed the Questionnaire for the Diagnosis of Urinary Incontinence. The prevalence and the factors associated with each form of UI were explored using multivariable weighted logistic regression. Results: 59.3% of the women were premenopausal, 8.4% perimenopausal and 32.3% postmenopausal. 83.2% had a BMI < 28 kg/m 2 and none were using menopausal hormone therapy. The prevalence of stress UI was 5.4% (95% CI 4.4–6.6%), urgency UI 11.3% (9.8–12.9%), and mixed UI 7.0% (5.8–8.3%). Urgency UI was the most prevalent form of UI at each decade of age. Postmenopausal women were significantly more likely to have urgency UI (AOR 2.41, 95%CI 1.38–4.20; p = 0.002) and mixed UI (AOR 2.35, 95%CI 1.22–4.50; p = 0.010). Having more than 2 children was significantly associated with stress UI (AOR 2.79, 95%CI 1.30–6.00; p = 0.009) and urgency UI (AOR 2.34, 95%CI 1.28–4.30; p = 0.006), pelvic organ prolapse with stress UI (AOR 2.46, 95%CI 1.34–4.52; p = 0.004) and mixed UI (AOR 3.40, 95%CI 2.00–5.80; p < 0.0001), and diabetes with mixed UI (AOR 3.16, 95%CI 1.67–5.97; p < 0.0001). The women in the highest wealth quintile (AOR 0.27, 95%CI 0.10–0.72; p = 0.009) and underweight women had a lower risk of urgency UI (AOR 0.21, 95%CI 0.06–0.77; p = 0.018), while urgency UI was associated with working outside the home (AOR 3.11, 95%CI 1.36–7.15; p = 0.007) and obesity (AOR 3.00, 95%CI 1.57–5.74; p = 0.001). Conclusions: The overall prevalence of UI amongst Bangladeshi midlife women is low, with urgency UI the most common form, in contrast to developed countries, where stress UI predominates. Being postmenopausal, having more than two children, being obese and working outside the home increase the likelihood of urgency UI, whereas higher socio-economic status and lower weight appear to be protective. Menopausal hormone therapy use was not reported by any study participants.